Analisis Tingkat Keterampilan Motorik Kasar Pada Siswa Ekstrakurikuler Pencak Silat Di Sekolah Dasar - Raynata, Chandra Galih; Wijaya, Andhega (Jurnal Sporta Saintika, 2025)
Motor skills play an important role in daily activities. One of the activities that can improve gross motor skills is pencak silat. The purpose of this study is to identify the level of gross motor skills and the factors that influence gross motor skills in students participating in pencak silat activities. The type of this research is cross-sectional. The instruments in this study consist of the gross motor development-2 test and This research was conducted at SDN Manguharjo, Madiun City. With subjects consisting of 35 students, including 15 male students and 20 female students. The research findings indicate that the level of gross motor skills of students participating in the pencak silat extracurricular at SDN Manguharjo Kota Madiun falls into the average category. Meanwhile, the factors influencing gross motor skills are human factors (students and coaches) with a p-value of 0.019 and method factors (training program) with a p-value of 0.033. In addition, this study also shows that the effective contribution of the human factor to the development of gross motor skills is 40.5%, which means that the human factor is the most dominant factor influencing gross motor skills.